Developing Persian Quick Speech in Noise With Words Containing High Frequency Phonemes: Determining its Validity and Equivalency - Farzaneh Fatahi; Atefeh Abolhasani Zeraatkar; Maryam Amiri Jahromi; Fahimeh Hajiabolhassan; Amirsalar Jafarpisheh; Nariman Rahbar; Elham Faghihzadeh (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims The quick speech in noise (Q-SIN) test shows how difficult it is to perceive speech in noise by determining signal-to-noise ratio (SNR) loss. The lists with high-frequency words have a better ability to identify SNR loss which have been created in Persian. Although a Persian version of Q-SIN with emphasis on high frequency is available، but there is no Q-SIN lists with high-frequency words; therefore,this study aims to develop new lists and the lists with high-frequency words for Q-SIN test and determine their equivalency in normal-hearing people which was condcuted in Tehran University of Medical Sciences.Methods The sentences were first developed. Then, their content validity and face validity were determined. In this regard، 36 sentences were used to make new Q-SIN lists and 36 sentences were used to make Q-SIN lists with high-frequency words. Based on the Q-SIN test development criteria، six regular lists (lists 1-6) and six lists with high-frequency words (lists 7-12) were tested on 46 people (23 males and 23 females) aged 18-35 with normal hearingResults The content validity index for new and high-frequency words lists were 0. 74 and 0. 736، respectively. The equivalency test results showed that among the first 6 lists، the lists no. 1, 2, 3, and 4 were equal. Among the six lists with high-frequency words, the lists no. 7, 8, 10, 11 were equal. There was no gender differences between six regular lists and high-frequency lists (P>0.05). Conclusion The Q-SIN word lists with equivalency can be used for normal-hearing people in clinical practice.